2014
DOI: 10.15274/inr-2014-10079
|View full text |Cite
|
Sign up to set email alerts
|

Is Intervertebral Cement Leakage a Risk Factor for New Adjacent Vertebral Collapse?

Abstract: This retrospective study evaluated the relationship between intervertebral cement leakage and new adjacent vertebral fracture and describes the different characteristics of cement leakage. Increased risk of new adjacent vertebral fracture (NF) has been reported to be a complication of cement leakage in vertebroplasty. In our observation, an incidental intervertebral cement leakage may occur during vertebroplasty but is commonly asymptomatic. The study focused on ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, bone cement is prone to leakage during the procedure, and detecting the leakage is challenging [34] . Churojana et al [35] found that cement leakage into the intervertebral disc did not increase the risk of NVCF. In contrast, a retrospective analysis conducted by Choi et al [36] in 2022 demonstrated that bone cement leakage was a risk factor for recurrent vertebral fractures during a one-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…However, bone cement is prone to leakage during the procedure, and detecting the leakage is challenging [34] . Churojana et al [35] found that cement leakage into the intervertebral disc did not increase the risk of NVCF. In contrast, a retrospective analysis conducted by Choi et al [36] in 2022 demonstrated that bone cement leakage was a risk factor for recurrent vertebral fractures during a one-year follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…However, bone cement is prone to leakage during PKP and leakage detection is challenging [ 36 ]. Churojana et al [ 37 ] found that cement leakage into the intervertebral disc did not increase the risk of NVCF. In contrast, a retrospective analysis conducted by Choi et al [ 38 ] reported a strong correlation between bone cement leakage and recurrent vertebral fractures at 1-year follow-up, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of different inclusion criteria, studies have reported the risk of an adjacent fracture after PVP may increase with a lower BMD (6,(16)(17)(18), greater age (16,19), female gender, and cement leakage to disc (19,20), intervertebral vacuum (16), lower BMI (21), increased preoperative segmental kyphosis (22), greater anterior height restoration rate (18), the distribution of cement within the fracture (23) and a larger number of fractures (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%